COMPARISON OF AEROKEYII SCHEME AND API20E SYSTEM FOR IDENTIFICATION OF AEROMONAS HYDROPHILA ISOLATED FROM WELLS WATER IN THIQAR PROVINCE-IRAQ - Muslim Dhaher Musa; Waffa Abdulelah Ahmed (Basrah Journal of Veterinary Research)
Untreated water is well-known source of A.hydrophila which is in addition to its enteropathogenicpotential ,also display resistance to commonly used antibiotics , so this study aimed to compare AerokeyII and API20E in identification of A.hydrophila with studying of some virulence factors andantibiogram profile in untreated wells water in Thi-Qar province. Isolation was conducted by employingAmpicilin Blood Agar (ABA30) and MacConkey agar medium, the suspected colonies were identifiedby using biochemical scheme (AerokeyII) , and API20E . The results of this study revealed thatA.hydrophila was recovered from 8 out of 30 wells with incidence rate (27.6%), incidence variation wasnoted among different regions which was statistically significant . All isolates showed β-hemolysis ofhuman erythrocytes , 75% have proteolytic activity and 50% of isolates were DNase positive. Resultsof Antibiogram analysis revealed that all isolates exhibit resistance in percentage (100%) to fiveantibiotics including ;Clindamycin , Cephalothin , Vancomycin , ticarcilin-clavulanic acid , Ceftazidime,and the resistance to Cefoxitin was 75%, while all isolates were (100%) susceptible to Gentamicin ,Amikacin, Chloramphenicol, Ofloxacin ,Ciprofloxacin, Naldxic acid, Imipenem , Norfloxacin, andDeoxycyclin. The susceptibility to Ceftriaxone was 62.5% , Streptomycin 87.5% and Trimethoprime87.5% . The study concluded that , high correlation between Aerokey II and API20E in identification ofA.hydrophila and untreated wells water are an important source of multi-drug resistant enteropathogenicA.hydrophila which pose public health threat especially to individuals using this kind of water source